Advances in information and communication technologies for adapting agriculture to climate change II : proceedings of the 2nd International Conference of ICT for Adapting Agriculture to Climate Change (AACC'18), November 21-23, 2018, Cali, Colombia /: proceedings of the 2nd International Conference of ICT for Adapting Agriculture to Climate Change (AACC'18), November 21-23, 2018, Cali, Colombia. ([2019]) - Unknown
No abstract available